Prevalence of Atherosclerosis in Psoriatic Patients Detected with Epiaortic Color Doppler Ultrasound and Computed Tomography Angiography - Dattola, Annunziata; Manenti, Guglielmo; Ferrari , Donatella; Vollono , Laura; Marsico , Salvatore; Lamacchia, Feliciana; Esposito , Maria; Marchesano , Mattia; Zangrilli , Arianna; Floris , Roberto; Giunta , Alessandro; Bianchi , Luca (Dermatology Practical & Conceptual, 2022)
Introduction: Psoriasis (PsO), a chronic inflammatory, multisystemic, and multifactorial disease can cause endothelial dysfunction, artery calcification, and atherosclerotic disease. A higher incidence of vascular occlusive events has been observed in psoriatic patients compared to healthy controls, and multiple studies confirm the association between moderate-severe PsO and atherosclerosis, coronary artery calcification, and higher cardiovascular risk.Objective: We sought to analyze atherosclerotic disease prevalence in epiaortic vessels of psoriatic and non-psoriatic patients to understand if PsO could represent an independent risk factor predisposing to atherosclerotic disease.Methods: We evaluated 47 psoriatic patients without cardiovascular risk factors with color Doppler ultrasound (CDUS). If atheromatous plaques were detected, a computed tomography angiography (CTA) was performed. We evaluated 47 non-psoriatic patients without cardiovascular risk factors with CDUS. Atherosclerosis prevalence in both groups were statistically analyzed. CDUS performance was compared to CTA.Results: In the psoriatic group (mean age 50.9 years), 6 had atheromatous plaques and 12 had an intima-media thickness (IMT) > 1 mm (overall prevalence of atherosclerotic disease: 38.2%). All plaques detected with CDUS were confirmed at CTA. In the control group (mean age 51.3 years), CDUS revealed atheromatous plaques in 4 patients and IMT > 1 mm in 4 ones (overall prevalence of 17%). The difference of atherosclerotic disease prevalence between the groups was statistically significant (P < 0.05).Conclusion: Our results highlight that PsO could be considered a predisposing factor for atherosclerotic disease development in epiaortic vessels, as it causes an increased IMT, that is also considered an independent cardiovascular risk factor.